(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2018)
While many corpus stylistic studies that draw on keywords pay attention to meanings of the lexical items, the present study focuses on their grammatical forms and argues that the forms largely account for the significance of keywords of a text and their contributions to meanings in a literary text. The nouns “years” and “man”, which were found to be statistically significant in Jane Austen’s Persuasion, were studied in terms of their co-occurrence patterns and textual functions. Concordance lines of these two words were analysed in comparison with their singular and plural non-key counterparts. The analysis reveals that the singular and plural forms of the keywords play an important role in the construction of thematic meanings and narrative techniques in the novel. It is suggested that an examination of grammatical aspects of keywords can provide contributions not only to literary studies of a novel but also to corpus stylistic methods and to theoretical linguistic arguments on word meanings.